FAKTOR DETERMINASI FUNGSI INTERMEDIASI PERBANKAN SYARIAH DI INDONESIA - Eva Eflinda; Prihantoro Prihantoro (Jurnal Ilmiah Ekonomi Bisnis, 2019)
The condition of national economic growth has not had a significant impact on improving the community economy. One of the indications can be seen from the high level of open unemployment in 2009. This happened because of complaints from businessmen who felt the difficulty to obtain capital injection from bank as an important source for increasing their production capacity. So that, the intermediation function of Indonesian banking still needs to be questioned. Especially in syariah banking, the role of intermediation function can be seen from the Financing to Deposit Ratio (FDR) indicator. FDR of syariah banking in 2009 showed a degredation from previous years. It indicates a further gap between collected and channeled funds through financing in syariah banking. So it is possible to make a study about the analysis of factors that can affect the banking intermediation function, especially syariah banking. This study aims to identify the factors that influence the intermediation function of syariah banking in Indonesia. The analytical tool used in this study is the "distributed-lag model" model. In this model the analysis carried out multiple linear regression analysis, multiple correlation, calculation of determination coefficient value, and hypothesis check with T-test and F-test. The conclusion is about the existence of  a significant relationship between NPF, SBIS, GDP and CSPI in cooperation with FDR. Partially, NPF has a significantly positive relationship with FDR, meanwhile SBIS and IHSG have a significantly negative relationship with FDR, and for GDP there is no significant relationship with FDR.